FRI0369 Effect of canakinumab vs triamcinolone acetonide for treatment of gouty arthritis in patients who are unable to use nsaids and colchicine or with severe gouty arthritis. (23rd January 2014) - Schlesinger, N.; Alten, R.; Bardin, T.; Bloch, M.; Shpilsky, A.; Krammer, G.; Kiechle, T.; So, A.
Abstract : Background: Treatment choice is limited in many gouty arthritis (GA) patients (pts) due to contraindications, intolerance or unresponsiveness to both NSAIDs and colchicine as well as in pts with severe GA. Canakinumab (CAN), a fully human monoclonal anti-IL-1β antibody, may be a potential treatment option for these pts. Objectives: To evaluate the efficacy and safety of CAN vs triamcinolone acetonide (TA) in a subgroup of pts who are unable to use NSAIDs and colchicine or with severe GA. Methods: In two, 12-week multi-center, double-blind, double-dummy, active controlled studies, pts ≥18-≤85 years meeting ACR 1977 preliminary criteria for GA and contraindicated, intolerant or unresponsive to NSAIDs and/or colchicine, with an onset of flare ≤5 days (d) were randomized to receive a single dose of CAN 150mg sc or TA 40mg im, and were re-dosed "on demand" on each new flare. Pts completing the core studies were enrolled into 12-week extension studies to further investigate "on demand" use of CAN 150mg sc or TA 40mg im on new flare. This retrospective pooled analysis compares efficacy and safety of CAN vs TA in the subgroup defined as "pts unable to use NSAIDs and colchicine or with severe GA" with at least one of the following baseline conditions: contraindication, intolerance or lack of efficacy of both NSAIDs and colchicine; >6 flares in the last year; ≥4 joints affected by acute attack or tophi present. Results: Of the 454 GA pts enrolled, 312 were considered unable to use NSAIDs and colchicine or with severe GA at baseline: 154 pts (49%) CAN group and 158 pts (51%) TA group. The mean pain intensity post-dose on visual analog scale at 72h and 7d was significantly lower for CAN vs TA (LS mean: 26.8 vs 38.4, p=0.0001 at 72h and 17.5 vs 26.1, p=0.0029 at 7d). After 24 weeks there was a statistically significant risk reduction of 47% for time to first new flare with CAN vs TA (hazard ratio 0.53; 95% CI 0.37 to 0.75; p=0.0001 [one sided]). C-reactive protein (CRP) and serum amyloid A (SAA) levels were significantly lower at 72h and 7d post-dose with CAN vs TA (CAN/TA ratio at 72h: CRP 0.65, p<0.0001; SAA 0.42, p<0.0001; at 7d: CRP 0.43, p<0.0001; SAA 0.30, p<0.0001). Adverse events (AEs) reported in >5% pts were arthralgia (5.8%), headache and back pain (5.2% each) in CAN group and hypertension (5.7%) in TA group. Infections and infestations were reported in 22.7% CAN vs 12% TA pts (upper respiratory tract infection, 2.6% vs 2.5%). Serious AEs were reported in 7.1% and 4.4% pts treated with CAN and TA, respectively. Of these events, 1.3% was infections such as pneumonia (0.6%) and gastroenteritis (0.6%) reported in CAN group. One death was reported in TA group (pulmonary embolism). Conclusions: Pts unable to use NSAIDs and colchicine or with severe GA when treated with CAN had significantly reduced risk of new flare and better pain relief compared to pts treated with TA. CAN may represent a potential treatment alternative for this subpopulation. Disclosure of Interest: N. Schlesinger Grant/Research support from: Novartis, Consultant for: Novartis, URL Pharma, Savient, Takeda, Rx Enzyme, Speakers Bureau: Novartis, Takeda, Savient, R. Alten Grant/Research support from: Novartis, Consultant for: Novartis, Speakers Bureau: Novartis, T. Bardin Grant/Research support from: Menarini, Consultant for: Novartis, Ipsen, Menarini, Ardea, Biocryst, M. Bloch Grant/Research support from: Novartis, A. Shpilsky Shareholder of: Novartis, Employee of: Novartis, G. Krammer Shareholder of: Novartis, Employee of: Novartis, T. Kiechle Shareholder of: Novartis, Employee of: Novartis, A. So Grant/Research support from: Novartis, Consultant for: Novartis, Ardea, Speakers Bureau: Novartis, Ardea, Menarini